Efektivitas Scaffolding dalam Pembelajaran Struktur Aljabar: Studi Mahasiswa Pendidikan Matematika Universitas HKBP Nommensen Pematangsiantar - Winnie Wie; Elice Twenty Saragih; Anemsinta Naibaho; Jernita Sihotang; Tara Agustian Siahaan; Christa Voni Roulina Sinaga (Young Journal of Social Sciences and Humanities, 2025)
Learning algebraic structures is often considered difficult for students to understand because of its abstract and theoretical nature. Without the right approach, students can find it difficult to relate theory to practice and master the basic concepts in algebraic structures. This article aims to examine the effectiveness of the application of the scaffolding method in learning algebraic structures. This study uses a qualitative approach by collecting main data through interviews with students of Mathematics Education at HKBP Nommensen University. The data analysis techniques used include data interpretation, data reduction, and conclusion drawn. The findings of the study show that the application of scaffolding provides more effective understanding for students, helping them overcome difficulties in learning complex material. In addition, scaffolding also increases students' interest in learning and makes learning algebraic structures more fun. Thus, this study confirms that scaffolding is an effective method to increase understanding and motivation for learning in learning algebraic structures.